2009
DOI: 10.1177/0022034509344559
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Therapy Improves Gastric Helicobacter pylori Eradication

Abstract: The oral cavity has been proposed as a reservoir for H. pylori that could be responsible for the refractoriness of gastric infection to triple therapy (antibiotics, antimicrobials, and proton pump inhibitors). The aim of this study was to evaluate the efficiency of combined periodontal and triple therapy vs. triple therapy alone, in gastric H. pylori eradication in persons with H. pylori in the subgingival biofilm. Individuals positive for H. pylori in their gastric and oral samples, as determined by nested PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 29 publications
5
77
1
Order By: Relevance
“…Eradication of oral H. pylori is effective in preventing the reappearance of gastric H. pylori infection from the oral cavity reservoirs. [31] In our study, patients with no history of eradication therapy for H. pylori were selected.…”
Section: Discussionmentioning
confidence: 99%
“…Eradication of oral H. pylori is effective in preventing the reappearance of gastric H. pylori infection from the oral cavity reservoirs. [31] In our study, patients with no history of eradication therapy for H. pylori were selected.…”
Section: Discussionmentioning
confidence: 99%
“…in contrast, Zaric et al (26) communicated that periodontal treatment in combination with systemic therapy could be a promising approach to increasing the therapy efficacy and decreasing the risk of infection recurrence. 77.3% of the patients treated with combined periodontal therapy exhibited successful eradication of gastric H. pylori, compared with 47.6% who underwent only triple therapy (26). Similar results were obtained by Jia et al (15).…”
Section: General Treatment Rulesmentioning
confidence: 98%
“…After the eradication therapy, H. pylori was not detected in the oral cavity, which suggests high effectiveness of the therapy protocol in the oral cavity, or it is possible that oral H. pylori is of a transient character (2). in contrast, Zaric et al (26) communicated that periodontal treatment in combination with systemic therapy could be a promising approach to increasing the therapy efficacy and decreasing the risk of infection recurrence. 77.3% of the patients treated with combined periodontal therapy exhibited successful eradication of gastric H. pylori, compared with 47.6% who underwent only triple therapy (26).…”
Section: General Treatment Rulesmentioning
confidence: 99%
“…Recently it was reported that plaque control results in lesser prevalence of H. pylori in the gastric mucosa (Jia et al, 2009). Another study reported that 77.3% of the patients treated using a combination of periodontal treatment and triple therapy exhibited successful eradication of gastric H. pylori, compared with 47.6% who underwent only triple therapy (Zaric et al, 2009). …”
Section: Effects Of Periodontal Therapy On the Management Of H Pylormentioning
confidence: 99%